Genital Infections and Infertility - Darwish, Atef M. (IntechOpen, 2016)
This book highlights the impact of genital tract infections on female infertility, male infertility, and even veterinary infertility. A comprehensive source on genital infections essential for all infertility specialists is now at your hands.